AN ANALYSIS OF OBSTACLES OF QUALITY MANAGEMENT SYSTEM APPLICATION ISO 9001:2008 AT SMK SMTI BANDAR LAMPUNG - Fitriah Wulandari (Prosiding International conference on Information Technology and Business (ICITB), 2015)
The focus of the research is SMK SMTI Bandar Lampunghas applied SMM ISO 9001:2008. The objectives of theresearch are 1) to have description on a commitment indecision making and executive personnel in implementingSMM ISO 9001:2008, 2) to have description on schoolmanagement efforts especially quality vice managementin handling existing obstacles, and 3) to have descriptionof effects of SMM ISO 9001:2008 implementation atSMK SMTI Bandar Lampung.The method used in the research uses a qualitativeapproach of case study. The data collecting techniquesused are interview, observation, and document analysisbased on theme. To gain the data validity the triangulationis used. The research sample is taken by using purposivesampling technique i.e. headmaster section, vice qualitymanagement, curriculum and student affairs.The result of the research indicates that the firstcommitment of the decision maker and executivepersonnel in the implementation of SMM ISO 9001:2008is not optimal, so (a) the achievement of vision is notmade; (b) the quality target is not recapitulated based onthe schedule, it is caused by lack of executive personnel sknowledge on SMM ISO 9001:2008 and the lack ofTUPOKSI of the executive personnel which causesoverloaded works to particular executive personnel; (c)several quality targets are not reached especially atinternal student customer satisfaction on the teacher s jobperformance and extracurricular activities, it is caused byweak monitoring and being infirm of the leader towardlaw/rule-breaking; (d) the internal audit finding andexternal audit finding working on similar problems andthe awareness to follow up the finding forced. Both effortsof vice quality management are (a) monitoring is includedinto the element of quality target counting, (b) revisingVision, Mission and Target of Quality of the school, (c)doing coaching over sections completely on responsibilitytaker and executive personnel, adding information onSMM ISO by sticking banners, making proposals ontraining activity or workshop as refreshment of SMMISO. (d) Updating TUPOKSI and decreasing teachingtime for functional teachers who are also in charge ofadministrative works. Third, (a) boosting public trust tosend their children to school at SMK SMTI BandarLampung, (b) increase the school quality image whichgives impacts on the trust of business world and industrialworld, (c) increasing the graduate quality (d) documentingpolicy, Procedure and IK connected with the high qualitydocumentation, (e) having a target or well plannedworking program , (f) increasing human resources qualitythrough education and resources of facility and infrastructuregetting better every year.KEY WORDS : SMM ISO 9001:2008, Analysis ofSMM obstacles